PERLINDUNGAN HUKUM DALAM PERJANJIAN KERJASAMA OBYEK WISATA TERAS SAWAH CEKING ANTARA DESA ADAT TEGALALANG DAN DESA ADAT KEDISAN KABUPATEN GIANYAR BALI - Kadek Apriliani; Putu Angga Pratama Sukma; Putu Bagus Dananjaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Tourism sector development contributes to regional income growth. One example is Gianyar Regency, which has various tourist destinations, including the Ceking Terrace Tourist Attraction. This destination is famous for its terraced views located in Kedisan Traditional Village, Tegallalang District. This research discusses the regulation and implementation of the profit-sharing agreement in the management of the Ceking Terrace Tourist Attraction. The method used is empirical legal research. The results of the study show that the legal regulation regarding the profit-sharing in the management of this tourist attraction is governed by the Gianyar Regency Regional Regulation No. 10 of 2013. This regulation stipulates that traditional villages and traditional institutions have rights within the profit-sharing system for managing this tourist attraction. The profit-sharing agreement includes the rights and obligations of the involved parties, including the management body of the Ceking Terrace Tourist Attraction, which is entitled to guarantees as per the agreed contract. The management body is also obligated to ensure the smooth operation of the management. Additionally, landowners are entitled to compensation for the rice fields used as tourist attractions, with the obligation to maintain its beauty in accordance with the agreement